Professional - "Bagchi, Subroto" (New Delhi, 2009)
In the new era, where every person's actions have the potential to have a global impact, we must redefine what it means to be a true professional. By common definition, a professional is someone who possesses the skills and knowledge necessary to do a job-whether it's a top degree from a prestigious university or simply years of on-the-job training. For centuries, we have relied on this definition to help us determine who is capable and who is not, often assuming that the person with the most professional characteristics is the best for the job. But every day we see examples of so-called professionals who do more harm than good: a few irresponsible bankers whose get-rich-quick schemes led to a global financial meltdown; a once-respected hedge fund manager charged with running the world's largest Ponzi scheme and robbing his clients of billions; a team of executives siphoning funds from their employees' pension plans . . . the list goes on. All of these people had the qualities necessary to do their jobs well, but instead they chose to abuse and corrupt their professions for their own personal gain. So how can we weed out the best from the worst when the accepted standards are no longer enough, and when even the most powerful and respected among us cannot be trusted? According to businessman and bestselling author Subroto Bagchi, the first step is to redefine what it means to be a professional. Today, it takes more than just aptitude-it takes a commitment to do what's right, not only for your business, but for society as a whole. The Professional outlines the explicit and implicit code of conduct.This is a must read for anyone looking for a little clarity in an increasingly blurry world.
Keywords: Personality